2019
DOI: 10.1186/s13045-019-0719-4
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanism of action of domatinostat (4SC-202) in cutaneous T cell lymphoma cells

Abstract: BackgroundTargeting epigenetic modifiers is effective in cutaneous T cell lymphoma (CTCL). However, there is a need for further improvement of this therapeutic approach. Here, we compared the mode of action of romidepsin (FK228), an established class I histone deacetylase inhibitor, and domatinostat (4SC-202), a novel inhibitor of class I HDACs, which has been reported to also target the lysine-specific histone demethylase 1A (LSD1).MethodsWe performed MTS assays and flow cytometric analyses of propidium iodid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 87 publications
4
27
0
Order By: Relevance
“…Indeed, proliferation and viability assays using several different techniques suggests that 4SC-202 is both cytotoxic and cytostatic in two-and three-dimensional cell culture models. In a number of different cancer models studies, 4SC-202 exerts both cytotoxic and cytostatic effects and arrested cell growth in the G2M phase [46]. In this study, 4SC-202 exerted cytostatic properties in the ATRT three-dimensional scaffold model, confirming results obtained in the two-dimensional cell culture.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, proliferation and viability assays using several different techniques suggests that 4SC-202 is both cytotoxic and cytostatic in two-and three-dimensional cell culture models. In a number of different cancer models studies, 4SC-202 exerts both cytotoxic and cytostatic effects and arrested cell growth in the G2M phase [46]. In this study, 4SC-202 exerted cytostatic properties in the ATRT three-dimensional scaffold model, confirming results obtained in the two-dimensional cell culture.…”
Section: Discussionsupporting
confidence: 85%
“…Domatinostat (4SC-202), a class I histone deacetylase/LSD1 dual inhibitor, is currently under assessment in phase I trial in patients with advanced hematological malignancies [118]. Wobser et al recently reported that 4SC-202 directly inhibited microtubule formation and effectively suppressed growth of cutaneous T cell lymphoma (CTCL) cells [119]. Studies have showed that LSD1 mediates epidermal growth factor (EGF) signaling, LSD1 knockdown or inhibition suppressed both intrinsic and EGF-induced cell migration in SKOV3 and HO8910 cells [120].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Originally believed to impair the function of the epigenetic eraser lysine-specific demethylase 1 (LSD1) which participates in the CoREST complex formation alongside HDACs 1 and 2, the class I HDACi unexpectedly turned out to inhibit tubulin polymerisation as well. Ongoing clinical trials in Phases I and II investigate its efficacy in hematological and gastrointestinal cancers [258,259].…”
Section: Hdac-lsd1 Inhibitormentioning
confidence: 99%